Seroprevalence of infectious agents affecting the reproductive system of water buffaloes (Bubalus bubalis) in Costa Rica - Rivera, Josué (2025)
Water buffaloes (Bubalus bubalis) are susceptible to most pathogens affecting cattle, leading to reproductive problems and decreased productivity, which significantly impacts livestock production. So far, the prevalence of brucellosis is the only pathogen that has been determined for this population in Costa Rica. The objective of this study was to determine the seroprevalence of bovine leukosis virus (BLV), bovine herpes virus type 1 (BHV-1), bovine viral diarrhea virus (BVDV), and Neospora caninum in buffaloes in Costa Rica. A total of 372 blood samples were collected from buffaloes older than 15 months across 20 farms in the provinces of Alajuela, Guanacaste, San José, Heredia, Limón, and Puntarenas between May and August 2020. The blood samples were analyzed using commercial enzyme-linked immunosorbent assays (IDvet, Montpellier, France) to determine each agent’s overall and farm-level seroprevalence. The assessed seroprevalences for BHV-1, BVDV, and N. caninum were 54.0%, 41.7%, and 64.3%, respectively. Seropositive individuals for BHV-1, BVDV, and N. caninum were identified in all provinces analyzed. The highest prevalence for BHV-1 was found in Alajuela (65.3%), Heredia (52.8%), and Limón (45.4%); for BVDV in San José (68.2%) and Alajuela (63.9%); and for N. caninum in San José (86.4%), Alajuela (69.4%), Guanacaste (66.6%), and Limón (61.4%). Among the farms analyzed 85.0%, 75.0%, and 100% tested positive for BHV-1, BVDV, and N. caninum, respectively. No BLV-positive animals were detected on any farm. This is the first study to report the prevalence of BHV-1, BVDV, and N. caninum in buffaloes from Costa Rica. These pathogens may contribute to farm reproductive problems, highlighting the need for further investigation into their effects to establish control and prevention programs.